2011
DOI: 10.1007/s11033-011-0721-6
|View full text |Cite
|
Sign up to set email alerts
|

Caudatin induces cell cycle arrest and caspase-dependent apoptosis in HepG2 cell

Abstract: In the present study, we investigate the anti-cancer activity and mechanism of caudatin, the C-21 steroidal glycosides, on human hepatoma cell line HepG2. The MTT assay and flow cytometry were used to evaluate HepG2 cell proliferation and cell cycle. Annexin-V/PI and DAPI staining were used to investigate cell apoptosis. Western blotting analysis was used to evaluate the expression levels of proteins. It is found that caudatin inhibits HepG2 cell growth and induces of G0/G1 phase arrest in a dose dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Nowadays, the use of apoptosis-inducing agents from herbal prescriptions has gained a great deal of interest for the treatment of cancer. These plant extracts have been explored for discovering potential natural therapeutic compounds due to their excellent pharmacological activities and low side effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the use of apoptosis-inducing agents from herbal prescriptions has gained a great deal of interest for the treatment of cancer. These plant extracts have been explored for discovering potential natural therapeutic compounds due to their excellent pharmacological activities and low side effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Caudatin, a C-21 steroidal glycoside, is mainly isolated from the root of Cynanchum bungei Decne in China. Recent studies demonstrated that caudatin induced the apoptosis of HepG2 cells or the SMMC772 cell line (6,7). Wang et al (8) found that caudatin had an inhibitory activity on the secretion of HBsAg and HBV DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we isolated four new C 21 -steroidal glycosides from the roots of Cynanchum auriculatum and reported the anticancer activity of auriculoside A (AA) which was the most active of the four (8,11,12). In the present study, CG, a C 21 -steroidal glycoside first isolated by Warashina et al in 1995, demonstrated greater cytotoxic effects than AA.…”
Section: Discussionmentioning
confidence: 99%